From astonishment to sublime: Schiller and the education through the “pathetic” - Machado, Felipe Tuller Moreira (Universidade Estadual de Campinas, 2020)
This article aims to propose a dialogue between the concept of “thaumázein” from Plato's Teeteto dialogue and Friedrich Schiller's notion of “sublime”, bringing them closer to the notion of “páthos”. The function of this debate will be to think about the associations between the terms and their function within the initiation into philosophy. At first, the context in which “thaumázein” appears in Plato will be discussed, then I will briefly present Schiller's notion of “sublime” in order to broaden it and locate its function within an educational perspective of the philosopher